2020
DOI: 10.1017/s002202992000031x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of high-starch and high-sugar diets on ruminal function in cattle

Abstract: The experiment reported in this research paper aimed to determine whether clinical and subclinical effects on cattle were similar if provided with isoenergetic and isonitrogenous challenge diets in which carbohydrate sources were predominantly starch or sugar. The study was a 3 × 3 Latin square using six adult Jersey cows with rumen cannulae, over 9 weeks. In the first 2 weeks of each 3 week experimental period cows were fed with a maintenance diet and, in the last week, each animal was assigned to one of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In our study, the concentration of Bas was increased in CRS, which was unexpected. Similarly, a previous study has shown that an increase in the count of circulating neutrophils was observed in cattle fed a high starch diet ( Francesio et al, 2020 ). It is possible that the high level of dietary starch may be a factor resulting in the increased concentration of Bas.…”
Section: Discussionsupporting
confidence: 69%
“…In our study, the concentration of Bas was increased in CRS, which was unexpected. Similarly, a previous study has shown that an increase in the count of circulating neutrophils was observed in cattle fed a high starch diet ( Francesio et al, 2020 ). It is possible that the high level of dietary starch may be a factor resulting in the increased concentration of Bas.…”
Section: Discussionsupporting
confidence: 69%
“…The cow milk production study could use a cross-over design (figure 9) as a diet intervention is considered reversible and a wash-out period equivalent to the diet exposure should be sufficient. 69 The experiment would take longer than a CRD approach, but far fewer animals would be needed. Wellek and Blettner 70 provide an efficiency conversion factor between a CRD and a two-period crossover design with a factor of interest with two levels using the measurement error and the between-subject variance.…”
Section: Case Study 2: Milk Production In Dairy Cowsmentioning
confidence: 99%
“…51 A recent study with non-lactating Jersey cows investigated the effects of two iso-energetic high-starch and high-sugar diets on ruminal pH and other health and fermentation parameters associated with ruminal acidosis. 52 Although the duration of ruminal pH below 5.8 was longer when 2.2 kg of the 5.53 kg of barley were replaced by molasses, thus aggravating the SARA, the acute phase response with the high-sugar diet (sugar content 176 g kg −1 DM versus 20 g kg −1 DM) was not as pronounced compared to that with the high-starch diet (starch content 599 g kg −1 DM versus 358 g kg −1 DM). It should be noted, however, that the starch content also of the high-sugar diet exceeded 300 g kg −1 DM, a level considered to increase the risk of SARA considerably.…”
Section: Characterization Of Plant Storage Carbohydratesmentioning
confidence: 99%